Эколого-морфологические особенности европейской лапи - Cervus (Dama) dama L.— в зоопарке «Аскания-Нова» - Кравченко, Р.С. (Вестник зоологии, 1971)
As a result of three-year observations of Cervus (Dama) dama L. in enclosures of
the zoo it was established that main biological rhythms (shedding of horns, autumn anci
spring moult, rut and calving) proceed in them for shorter periods of time than in other
species of Cervus elaphus L. and depend on age, fatness and physiological state. Some
peculiarities of Cervus (Dama) dama L. behaviour and the periods of biorhythms are
described. The experience of Cervus (Dama) dama L. breeding in enclosures testifies to
a high adaptability of the organism of these animals to the conditions of the South Ukraine.